Constructed Wetlands for Marine Aquaculture Wastewater Treatment: A New Challenge - Perez, Leonardo Martin (2021)
Aquaculture is the fastest growing food production sector worldwide. Global demand for seafood continues to grow, and landbased aquaculture is expected to grow in order to meet the increasing market demand. In this context, marine aquaculture production systems are moving towards land-based farming. However, due to the large volumes of wastewater with high salinity and other fish-metabolism derived pollutants (e.g., nitrogen compounds), it remains a challenge for treatment of effluents from land-based marine aquaculture. In this scenario, development of environmental-friendly and efficient aquaculture effluent treatment system is crucial for sustainable intensification of aquaculture. Owing to low capital, operating costs, and low energy consumption, constructed wetlands (CWs) are becoming a promising technique to treat aquaculture effluents before discharge.